Boris Pasternak wobec przemian cywilizacyjnych - Zbyrowski, Zygmunt (Studia Rossica Posnaniensia, 2019)
Boris Pasternak made use of available means of transport and communication on a daily basis. This fact, however, was not reflected in his autobiographical writings, correspondence and his oeuvre. The sole exception was the railway, playing a significant role in the life of the author and his protagonists as well as in the contents and form of his works.